2016
DOI: 10.11113/jt.v78.9165
|View full text |Cite
|
Sign up to set email alerts
|

SELF-CLEANING TiO2-SiO2 CLUSTERS ON COTTON TEXTILE PREPARED BY DIP-SPIN COATING PROCESS

Abstract: Titanium-silica (TiO2-SiO2), a type of semiconductor metal oxide cluster compound, has been widely used as oxidative catalysts and dye agents. In this research, TiO2-SiO2 on cotton textile has been utilized as self-cleaning agents by cross linking with acrylic acid compound. The clusters of TiO2-SiO2 was modified by a series of Ti:Si molar compositions, i.e. 1:1; 2:1 and 1:2. The successful modification of the cotton textile’s fiber surface was confirmed with an increase in mass. The FTIR spectra displayed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The inorganic UV-absorber ZnO is substantially stable against degradation and it is non-toxic. Rilda et al [155] prepared TiO 2 -SiO 2 powders by a sol-gel method to provide cotton fabric with a uniform coating by using a spin coater. The results showed that the TiO 2 -SiO 2 -coated cotton had a ratio of Ti:Si of 1:2, which achieved the best self-cleaning effect in the degradation of methylene blue.…”
Section: Uv Protection and Self-cleaningmentioning
confidence: 99%
“…The inorganic UV-absorber ZnO is substantially stable against degradation and it is non-toxic. Rilda et al [155] prepared TiO 2 -SiO 2 powders by a sol-gel method to provide cotton fabric with a uniform coating by using a spin coater. The results showed that the TiO 2 -SiO 2 -coated cotton had a ratio of Ti:Si of 1:2, which achieved the best self-cleaning effect in the degradation of methylene blue.…”
Section: Uv Protection and Self-cleaningmentioning
confidence: 99%
“…Rilda et al [48] previously produced TiO 2 -SiO 2 powder by using titanium isopropoxide and TEOS as precursors with different molar ratios, diethanol amine (DEA) as stabilizer, isopropanol as solvent, and chitosan in acetic acid as dispersing agent by sol-gel process. The fabric samples coated with acrylic acid binder were immersed to TiO 2 -SiO 2 suspension containing the powder, surfactant, and isopropanol and then coated with the suspension to ensure homogeneous coating by spin-coating machine.…”
Section: Uv Protection Self-cleaning and Soil Repellency (Photocatamentioning
confidence: 99%
“…The fabric samples coated with acrylic acid binder were immersed to TiO 2 -SiO 2 suspension containing the powder, surfactant, and isopropanol and then coated with the suspension to ensure homogeneous coating by spin-coating machine. Falling at absorbance of methylene blue under UV irradiation for 120 min was attributed to self-cleaning properties of fabrics treated with TiO 2 -SiO 2 powders with especially 1:2 molar ratios [48]. Wang et al [39] treated the cotton fabric with TiO 2 acidic hydrosol prepared with titanium (IV) butoxide as precursor by dip-pad-steam process.…”
Section: Uv Protection Self-cleaning and Soil Repellency (Photocatamentioning
confidence: 99%
“…The relevance of self-cleaning arises when the fabric is continually exposed to dust and there is not enough time to wash them. One of the advantages of self-clean finishing is the elimination of traditional laundry procedures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%